Quality and bioactive compound accumulation in two holy basil cultivars as affected by microwave-assisted hot air drying at an industrial scale - Wiset, Lamul; Poomsa-ad, Nattapol; Jindamol, Hathairut; Thongtip, Akira; Mosaleeyanon, Kriengkrai; Toojinda, Theerayut; Darwell, Clive Terence; Saputro, Triono Bagus; Chutimanukul, Panita (Frontiers in Sustainable Food Systems, 2023)
Holy basil (Ocimum Tenuiflorum L.) contains several bioactive compounds useful to the pharmaceutical and food industries. Microwave drying (MD) is a powerful technique for rapid drying of food or plant materials while preserving bioactive compounds during the process. However, little is known about the optimal combination of MD power with hot air drying (HAD) that can preserve the quality and yet only consume reasonable energy when drying holy basils. For that purpose, the effects of drying methods using MD combined with HAD at 45°C were examined to prevent losses in quality, antioxidant activities, and volatile flavor compounds in two holy basil cultivars (green and red cultivars). Holy basil leaves were dried at different MD powers of 200, 400, and 600 W combined with HAD and compared with a traditional tray drying (TD) at 45°C. Drying using MD at 600 W with HAD displayed significantly high levels of color retention, chlorophyll, and carotenoid content in both cultivars. The green cultivar showed a greater accumulation of total phenolic compounds (TPC), terpenoids, and DPPH free radical scavenging at 400 W with HAD. However, the red cultivar had the highest TPC, flavonoid, and terpenoid content at 600 W with HAD. The accumulation of major volatile organic compounds (VOCs) was also affected, and treatment at 600 W exhibited the highest methyl eugenol and β-caryophyllene content in both cultivars. The use of the highest power of MD (600 W) with HAD for leaf drying reduced the effective drying time and energy consumption among both cultivars. Taking into consideration the dried quality of antioxidant accumulation and energy consumed for drying, we recommend using MD at 400 or 600 W with HAD for the green cultivar and 600 W for the red.